Transcriptome and Differential Expression Profiling Analysis of the Mechanism of Ca2+ Regulation in Peanut (Arachis hypogaea) Pod Development - Yang, Sha; Li, Lin; Zhang, Jialei; Geng, Yun; Guo, Feng; Wang, Jianguo; Meng, Jingjing; Sui, Na; Wan, Shubo; Li, Xinguo (Frontiers in Plant Science, 2017)
Calcium not only serves as a necessary nutrient for plant growth but also acts as a ubiquitous central hub in a large number of signaling pathways. Free Ca2+ deficiency in the soil may cause early embryo abortion, which eventually led to abnormal development of peanut pod during the harvest season. To understand the mechanisms of Ca2+ regulation in pod development, transcriptome analysis of peanut gynophores and pods was performed by comparing the treatments between free Ca2+ sufficiency and free Ca2+ deficiency using Illumina HiSeq™ 2000. 9903082800nt bases are generated totally. After assembly, the average length of 102819 unigenes is 999 nt, N50 is 1782 nt. RNA-seq based gene expression profilings showed a large number of genes at the transcriptional level changed significantly between the aerial pegs and underground swelling pods under free Ca2+ sufficienct or deficienct treatments, respectively. Genes encoding key members of Ca2+ signaling transduction pathway, enzymes for hormone metabolism, cell division and growth, transcriptional factor as well as embryo development were highlighted. This information provides useful information for our further study. The results of digital gene expression indicated that exogenous calcium might contribute to the development of peanut pod through its signal transduction pathway, meanwhile, promote the normal transition of the gynophores to the reproductive development.